Quality by design-assisted green uv-spectrophotometric method development and validation for the quantitative estimation of letrozole - Pakali, Shahrikh S.; Palled, Mahesh; Suryawanshi, Shailendra S. (Drug Analytical Research, 2025)
Letrozole, a potent aromatase inhibitor, is commonly used in treating hormone-responsive breast cancer. With the rising incidence of breast cancer and increased demand for anticancer agents, this study aims to develop a green, cost-effective, and precise UV-spectrophotometric method for Letrozole estimation using Quality by Design (QbD) and Green Analytical Chemistry (GAC) approaches. A UV-spectrophotometric method was developed using an eco-friendly solvent system to improve the solubility and analytical efficiency of Letrozole. Method optimization was carried out using a QbD to ensure robustness and sustainability. The method was validated as per ICH Q2(R1) guidelines for linearity, accuracy, precision, specificity, and robustness, confirming its suitability for routine analysis. The developed method exhibited excellent linearity within the concentration range of 2–10 µg/mL, with a correlation coefficient (R²) of 0.9994. The limit of detection (LOD) and limit of quantification (LOQ) were determined to be 0.870 µg/mL and 2.021 µg/mL, respectively. Precision, robustness, and ruggedness assessments demonstrated percent relative standard deviation values below 2%, indicating high method reproducibility and reliability. The mean recovery values ranged from 99.71% to 102.40%, confirming the method’s accuracy. Furthermore, the assay of marketed formulations yielded consistent results, supporting the suitability of the method for routine quality control applications. A novel, simple, eco-friendly, and QbD guided UV-spectrophotometric method was successfully developed and validated for the estimation of Letrozole in bulk and pharmaceutical dosage forms. The method is suitable for routine analytical applications due to its precision, accuracy, and environmental sustainability.